Discursos da construção do outro : os povos indígenas nos Sermões - Melo, Hadassa Kelly Santos (2013)
The greatest legacy left by Father Antonio Vieira is certainly the vastness of his work. His sermons represent, to historians, a great possibility in terms of interpretation of the past and its contexts, and the processes involving encounters between Natives and Jesuits, in Portuguese America. Mutual resistance processes, which also include the production of representations in order to designate Natives, to provide them with meaning and interpret them, so that dialogues could take place. Throughout this paper, these aspects will be analyzed through representations Father Antonio Vieira set to natives during his missionary services in Maranhao and Grao-Para State (1652-1662). For this purpose, five sermons were chosen amongst those produced by the Father, Fifth Sunday of Lent (1654), Sexagesima (1655), First Octave of Easter (1656), Holy Spirit (1657) and Epiphany(1662). Such preaching expresses how the images built around natives were modified through time, not by the ongoing reflexions around their nature nor the procedures involving their evangelization, which obeyed demands that rose from conflicts with colonists, public authorities and other religious orders as in reference to native workforce usage and responding, as well, to instrumentalized resistance procedures from natives towards the Europeans ethos of living.